Lasing from dot-in-rod nanocrystals in planar polymer microcavities. Issue 23 (9th April 2018) - Manfredi, G.; Lova, P.; Di Stasio, F.; Rastogi, P.; Krahne, R.; Comoretto, D.
Abstract : We report on the production of an optically pumped vertical cavity laser made by polymer mirrors embedding inorganic core@shell nanocrystals. Abstract : Colloidal nanocrystals attract considerable attention in the field of light emitting devices thanks to their high fluorescence quantum yield, low amplified spontaneous emission (ASE) threshold, and spectral tunability via electronic structure engineering and surface functionalization. Combining polymer microcavities with colloidal nanocrystals as gain material promises a solution-based fabrication route to plastic laser cavities as well as applications in the field of smart flexible large area light sources and sensors. Here we demonstrate lasing from polymer microcavities embedding solution processable dot-in-rod (DiR) CdSe/CdS nanocrystals. Two highly reflective polymer dielectric mirrors are prepared by spin-coating of alternated layers of polyacrylic acid and poly( N -vinyl carbazole), with their photonic band gap tailored to the emission of the DiRs. The DiRs are enclosed in the polymer microcavity by drop-cast deposition on one mirror, followed by pressing the mirrors onto each other. We obtain excellent overlap of the ASE band of the DiRs with the photonic band gap of the cavity and observe optically pumped lasing at 640 nm with a threshold of about 50 μJ cm −2 .